A population pharmacokinetic study of benzathine benzylpenicillin G administration in children and adolescents with rheumatic heart disease: New insights for improved secondary prophylaxis strategies - Hand, R.M.; Salman, S.; Newall, N.; Vine, J.; Page-Sharp, Madhu; Bowen, A.C.; Gray, K.; Baker, A.; Kado, J.; Joseph, J.; Marsh, J.; Ramsay, J.; et al. (OXFORD UNIV PRESS, 2019)
Background: Benzathine benzylpenicillin G (BPG) is recommended as secondary prophylaxis to prevent recurrence of acute rheumatic fever and subsequent rheumatic heart disease (RHD). Following intramuscular injection, BPG is hydrolysed to benzylpenicillin. Little is known of the pharmacokinetics of benzylpenicillin following BPG in populations at risk of RHD.